Claiming prior consultation, monitoring environmental impact: counterwork by the use of formal instruments of participatory governance in Ecuador's emerging mining sector. Issue 5 (4th May 2017) - Leifsen, Esben; Sánchez-Vázquez, Luis; Reyes, Maleny Gabriela
Abstract: The last environmental impact assessment (EIA) related to Ecuador's first large-scale open pit copper mine, the Mirador project, was presented to the public in March 2015. In this article, we discuss how the rural mestizo population and Shuar indigenous people, who are under increasing pressure from the government and the mining company, contest the current politics of accountability related to the making and dissemination of this EIA. We analyse how formal instruments of governance related to participation (prior consultation) and environmental management (environmental impact monitoring), are re-used in the affected population's resistance work. We look at how these formal instruments are put to independent and political use as part of an extended struggle for influence over the process of transformation that the mega mining project generates. The article contributes to a discussion around participatory strategies that build on new conversations between 'popular environmentalists' and social/earth scientists.